Relationship between Knowledge, Attitude, and Preventive Measures against Dengue Hemorrhagic Fever in Community - Istiyarsih Sillia; Adrian Umboh; Novie H. Rampengan (Universitas Sam Ratulangi, 2022)
Abstract: North Sulawesi Province is included in the category with the highest cases of dengue hemorrhagic fever (DHF) in Indonesia. This study aimed to evaluate the relationship between know-ledge, attitude, and preventive measures against DHF in the community. Thia was an analytical and descriptive study with a cross sectional design. Respondents were people who lived in Puskesmas (primary health center) Kelurahan Sario Kotabaru Kota Manado area. There were 89 respondents in this study obtained by using incidental sampling technique. The results showed that DHF occurred in 5 respondents (5.6%). The majority of respondents had moderate knowledge (52.8%), agreeable attitude (70.8%), and moderate preventive measures (55.1%). Bivariate analysis resulted in significant relationship between knowledge and the occurrence of DHF (p=0.020); attitude and the occurrence of DHF (p=0.001); and preventive measures and the occurrence of DHF (p=0.016). Multivariate analysis using linear regression showed that attitude was the most related factor to DHF occurrence (Exp B=-0.034, regression coefficient =-0.140, p= 0.002). In conclusion, there is a relationship between knowledge, attitude, and preventive measures with DHF occurrence. Attitude is the most related factor to the occurrence of DHF in the community at Puskesmas Kotabaru area.Â Keywords: dengue hemorrhagic fever (DHF); knowledge; attitude; preventive measuresÂ Abstrak: Sulawesi Utara termasuk dalam salah satu provinsi di Indonesia dengan kategori kasus demam berdarah dengue (DBD) tertinggi. Penelitian ini bertujuan untuk mengetahui hubungan antara pengetahuan, sikap, dan tindakan pencegahan masyarakat terhadap DBD. Jenis penelitian ialah analitik deskriptif dengan desain potong lintang. Responden penelitian ialah masyarakat di wilayah Puskesmas Kelurahan Sario Kotabaru Kota Manado sebanyak 89 orang diperoleh dengan menggunakan teknik sampling insidental. Hasil penelitian menunjukkan kejadian DBD terdapat pada 5 responden (5,6%). Responden paling banyak terdistribusi pada pengetahuan cukup (52,8%), sikap setuju (70,8%), tindakan pencegahan cukup (55,1%). Hasil analisis bivariat menunjukkan adanya hubungan bermakna antara pengetahuan dengan kejadian DBD (p=0,020), sikap dengan kejadian DBD (p=0,001), dan tindakan pencegahan dengan kejadian DBD (p=0,016). Analisis multivariat menggunakan regresi liniear mendapatkan bahwa sikap merupakan faktor yang paling berhubungan dengan kejadian DBD (Exp B=-0,034, koefisien regresi=-0,140, dan nilai p=0,002). Simpulan penelitian ini ialah pada masyarakat di wilayah Puskesmas Kelurahan Sario Kotabaru terdapat hubungan antara pengetahuan, sikap, dan tindakan pencegahan dengan kejadian DBD. Sikap merupakan faktor yang paling berhubungan dengan kejadian DBD.Kata kunci: demam berdarah dengue (DBD); pengetahuan; sikap; tindakan pencegahan